AS POLÍTICAS EDUCACIONAIS DO ESTADO BRASILEIRO OU DE COMO NEGARAM A EDUCAÇÃO ESCOLAR AO HOMEM E A MULHER DO CAMPO - UM PERCURSO HISTÓRICO - Adelaide Ferreira Coutinho (EccoS – Revista Científica)
Throughout Brazilian history, education for those who live and work in rural areas was not seen as a priority to the government. For a long time, despite the economy being strongly based in agriculture, rural education was neglected in Brazilian legislation. When rural education begun to receive more focus, the intent was to stop rural flight, keeping population in farms in order to increase productivity. It can be seen that, since 1889, educational processes were developed in order to keep these men and women from wanting a different lifestyle. Despite city and countryside being part of the same reality, for decades, a vision of a rural school was prioritized, while under the urban paradigm, in order to comply with the interests of the industrial and agrarian sectors. This study takes a historic journey through this issue, highlighting the social movements that developed during the 90s, and their struggle for a rural education. This process resulted in the approval of educational policies. Among them are PRONERA (1998) and the Operational Guidelines for Basic Education in Rural Schools (2002). There is still much to be done for rural education, however, any action from the government will only achieve its goal if it is democratically offered, in all levels and types, and if placed on a new foundation, taking into consideration regional, social and cultural differences, as well as the organization of production.